Penerapan Аsаs-Аsаs Umum Pemerintаhаn yаng Bаik dаlаm Penyelesаiаn Sengketа Tanah Hak Milik - Ernanda, Dita; Istislam, Istislam; Yuliati, Yuliati (Universitas Negeri Malang, 2021)
This study aimed to describe the procedure for resolving land disputes, the application of the General Principles of Good Government (AUPB) in land dispute resolution, and the supporting and inhibiting factors for the application of AUPB in resolving land disputes. This study used a sociological juridical approach, with the type of empirical juridical research. The procedure for resolving land disputes was through two types of applications, namely letters of public complaints and implementation of court decisions. The application of AUPB in land dispute resolution started from the application, data collection and analysis, field assessment and inspection, case exposure, case settlement reports, settlement, and implementation of settlement decisions. Supporting factors for the implementation of AUPB were the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 11 of 2016, Section for Handling Land Problems and Control, as well as facilities and infrastructure for mediation, case titles, and transportation. The obstacle of the AUPB implementation included the inkracht decision to issue replacement certificates that had not been explicitly regulated, resulting in land registration services being blocked by the system and uncooperative parties.